A Framework of Zakat on Digital Assets in Malaysia: Perspectives of Millennials - Hanudin Amin (Journal of Islamic Monetary Economics and Finance, 2026)
This study examines the key factors influencing the acceptance of zakat on digital assets in Malaysia. It employs a modified Attitude-Social Influence-Efficacy (ASE) model and makes use of SmartPLS 4.0 to investigate the acceptance of zakat on digital assets among 440 millennial zakat payers. All factors derived from the ASE and the perceived fatwa legitimacy demonstrate significant relationships with such acceptance. Our findings have practical implications. For example, zakat institutions can enhance zakat on digital assets and utilization by applying key concepts from the ASE model and considering the importance of fatwa legitimacy.